2012
DOI: 10.4186/ej.2012.16.4.39
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ultrafine Copper Powders with Controllable Size via Polyol Process with Sodium Hydroxide Addition

Abstract: Abstract.A facile polyol process for producing copper powders with controllable size is described here. The copper powders have been readily synthesized by the reduction of copper (II) nitrate trihydrate with the solution of glycerol and sodium hydroxide. The X-ray diffraction, SEM and FESEM were used to characterize the obtained copper powders. The effect of the concentration of NaOH and the reaction temperature were investigated. The sizes and the complete reaction time of the copper powders were decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…No characteristic peaks indexed to copper oxide were observed, indicating the phase purity of copper metal. The results obtained are in strong corelation with previous reports [58,59]. However, differences in intensity and broadness in corresponding peaks were evident.…”
Section: Atomic Force Microscopy (Afm)supporting
confidence: 89%
“…No characteristic peaks indexed to copper oxide were observed, indicating the phase purity of copper metal. The results obtained are in strong corelation with previous reports [58,59]. However, differences in intensity and broadness in corresponding peaks were evident.…”
Section: Atomic Force Microscopy (Afm)supporting
confidence: 89%
“…The formation of zerovalent CuNPs can be explained by the chemical reduction of CuCl 2 · 2 H 2 O in the solution of hydrazine hydrate (NH 2 NH 2 · H 2 O) . It has been reported that in this reaction initially Cu 2+ ions were reduced to Cu + ions which precipitated as Cu 2 O particles, afterwards the reduction of cuprous oxide to copper metal powder occurred .…”
Section: Resultsmentioning
confidence: 99%
“…Cauliflower-like particles obtained under conditions of vigorous hydrogen evolution and dendrites are the most frequent shapes of electrolytically produced Cu particles. 10,18 Particles of spherical shape, such as globules, are usually formed by non-electrolytic methods of synthesis, such as the gas-atomizing process, 26 the polyol process 27 and ultrasonic spray pyrolysis. 28 Copper particles of spherical shape have been obtained by electrolysis processes only in the presence of additives, such as a combination of potassium ferrocyanide and 2,2′-dipyridine.…”
Section: Resultsmentioning
confidence: 99%